2017
DOI: 10.1111/jopy.12320
|View full text |Cite
|
Sign up to set email alerts
|

Trait and perceived environmental competitiveness in achievement situations

Abstract: These studies highlight the importance of attending to the interplay of the person and the (perceived) situation in analyses of competitive striving.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 88 publications
4
32
0
Order By: Relevance
“…In fact, examining the relationship between both psychometric self-reported and economic behavioral measurements, Bönte et al (2017a) report that self-reported measures of individual competitiveness can reflect a wide variety of motives for favoring competition and, in particular, are likely to reflect personal development motives. This is consistent with findings that self-reported attitudes toward competition significantly relate to achievement motivations (Elliot et al 2018). Furthermore, Bönte and Piegeler (2013) do not control for individuals' desire to win or the heterogeneity in individuals' expectations to win in competitions.…”
Section: Entrepreneurs' Enjoyment Of Competitionsupporting
confidence: 91%
“…In fact, examining the relationship between both psychometric self-reported and economic behavioral measurements, Bönte et al (2017a) report that self-reported measures of individual competitiveness can reflect a wide variety of motives for favoring competition and, in particular, are likely to reflect personal development motives. This is consistent with findings that self-reported attitudes toward competition significantly relate to achievement motivations (Elliot et al 2018). Furthermore, Bönte and Piegeler (2013) do not control for individuals' desire to win or the heterogeneity in individuals' expectations to win in competitions.…”
Section: Entrepreneurs' Enjoyment Of Competitionsupporting
confidence: 91%
“…It may also be that even though most students perceive their environment to be competitive, they may also perceive themselves as doing relatively well compared to the others, and the negative effects of competition may only arise when students know they are falling behind. In response to a meta-analytic finding of no (or small) influence of competitiveness on performance (Murayama & Elliot, 2012), performance goals were investigated as a potential mediator (Elliot, Jury, & Murayama, 2018). Elliot et al (2018) found that undergraduate psychology students who adopted performance approach goals in response to competitiveness performed better than students who adopted performance-avoidance goals.…”
Section: Discussionmentioning
confidence: 99%
“…In response to a meta-analytic finding of no (or small) influence of competitiveness on performance (Murayama & Elliot, 2012), performance goals were investigated as a potential mediator (Elliot, Jury, & Murayama, 2018). Elliot et al (2018) found that undergraduate psychology students who adopted performance approach goals in response to competitiveness performed better than students who adopted performance-avoidance goals. In light of this and given the mixed results in the literature on competitiveness in music education, we suggest caution in interpreting this result, and that further research more closely examines a range of outcomes and mediators that could potentially be associated with competitiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the perceived competitiveness and approach-avoidance motivation variables were self-reported. We argued that perceiving others as competitive in one's social environment predicts appetitive and aversive competitive motivation (i.e., the tested model), but others could argue that competitive motivations may predict the perception that others are competitive (i.e., reverse causation; see Elliot, Jury, & Murayama, 2018). However, from a theoretical perspective, perceived competitiveness is presumed to activate general competitive concerns, which are then regulated by appetitive and aversive competitive motivation, not vice versa (see Murayama & Elliot, 2012).…”
Section: Present Researchmentioning
confidence: 97%